Evaluation of Ionic Liquid-Modified Mesoporous Silica Particles for Separation of Polysaccharides - Zhang, H.; Lee, Y.R.; Row, K.H. (Asian Journal of Chemistry, 2015)
A group of ionic liquid-modified mesoporous silica particles was synthesized and characterized. A suitable sorbent with a suitable imidazole group and anion was selected according to its adsorption behaviour to the two polysaccharides on various synthesized particles. To confirm the conditions for the optimal adsorption capacity of the proposed sorbent, the standard/sorbent ratio, time and pH were investigated. The adsorption behaviour of these polysaccharides allowed the purification and separation of one compound from another and might find applications in extraction from natural plants in further studies.